2005
DOI: 10.1021/ie050432o
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Effects of CaO Additive on Atmospheric Gasification of Biomass at Different Temperatures

Abstract: Calcium oxide has long been recognized as an effective in-bed catalyst for reforming or cracking tars generated in thermally decomposing hydrocarbon fuels such as biomass. Under pressures as high as 20 atm, the oxide was also widely tested as a good CO 2 acceptor to capture CO 2 on-site to produce high-caloric pipeline gas from gasifying coal and coal-coke. By using CaO as an additive of the fuel and bed material, the research detailed in this research note demonstrated that CaO could also be a substantially g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 7 publications
6
37
0
Order By: Relevance
“…It may be noted that the type of gasifier, bed materials and biomass used shall affect the concentration of H 2 . The model results agree well with the experimental results from Mahishi and Goswami [20] and Xu et al (2005) [23] as shown in the table.…”
Section: Comparison With Similar Studies For Validationsupporting
confidence: 86%
See 2 more Smart Citations
“…It may be noted that the type of gasifier, bed materials and biomass used shall affect the concentration of H 2 . The model results agree well with the experimental results from Mahishi and Goswami [20] and Xu et al (2005) [23] as shown in the table.…”
Section: Comparison With Similar Studies For Validationsupporting
confidence: 86%
“…LHV (MJ/Nm 3 ) of syn gas produced via air-steam gasification can be augmented (from 5.58 to 6.12 for ER = 0.25, SBR = 1) with increase in CaO content (SOBR from 0.75 to 1.5) in the system. The reaction kinetic model is compared with experimental studies of Mahishi and Goswami [20] and Xu et al (2005) [23] and good agreement is observed. As an alternative to fossil fuel expended steam gasification, pure oxygen (or oxygen enriched air) gasification is suggested by the study, since comparable richness in H 2 in producer gas can be achieved by both.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Thereby the energy conversion efficiency was promoted by 14.2% compared with that without catalyst. Previous studies showed that the main components of calcined dolomite were CaO and MgO [35], in the surface of which many active sites with polarity could reduce the activation energy of tar cracking and reforming reactions by destroying the CeC and CeH bonds of tar components, thereby enhanced the transformation of tar into gases [37]. Fig.…”
Section: Effect Of Catalyst On Gasification Performancementioning
confidence: 97%
“…Detailed descriptions of the approach can be found in the literature [4,5]. Extensive research on biomass gasification with in situ CO 2 capture has been conducted using batch-type reactor [6][7][8], moving bed reactor [9] and fluidized bed reactor [10] under either atmospheric [6,9,10] or pressurized [7,8] …”
Section: Introductionmentioning
confidence: 99%